Manuscript PENGARUH FLEKSIBILITAS KERJA, STRES KERJA, DAN MINDFULNESS TERHADAP KEPUASAN KERJA TENAGA KESEHATAN DI PUSKESMAS SIWALAN KABUPATEN PEKALONGAN - Aknes Sintiya Dewi; Lana Adila; Arika Shafa Nabila; Faka Dzul Umam (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
Job satisfaction among healthcare workers is an essential determinant of service quality in primary healthcare facilities. Factors such as work flexibility, work stress, and have been associated with job satisfaction, yet empirical evidence in Puskesmas settings remains limited. This study analyzed the influence of work flexibility, work stress, and on job satisfaction among healthcare workers at Puskesmas Siwalan, Kabupaten Pekalongan. A quantitative cross-sectional study was conducted with total sampling of 40 healthcare workers. Data were collected using validated instruments: Workplace Flexibility Scale (Hill et al., 2001), Perceived Stress Scale (Cohen et al., 1983), Mindful Attention Awareness Scale (Brown & Ryan, 2003), and Job Satisfaction Survey (Spector, 1985). Data were analyzed using IBM SPSS Statistics 29 with multiple linear regression (α = 0.05). Work flexibility had a positive and significant effect on job satisfaction (β = 0.283; p = 0.048). Work stress had a negative and significant effect (β = –0.403; p = 0.005). had no significant effect on job satisfaction (p = 0.140). Together, the three variables explained 33.5% of the variance in job satisfaction. Job satisfaction among healthcare workers is significantly influenced by work flexibility and stress levels, while does not contribute significantly. Strengthening work arrangements and managing stress are essential strategies to improve job satisfaction in Puskesmas settings